AN ANALYSIS ON BARACK OBAMA'S SPEECH VIEWED FROM GRAMMATICAL COHESION - detti lismayanti (Edu-Ling: Journal of English Education and Linguistics, 2019)
The aim of this study is to find out what is the type, dominant and function on Barack Obama's speech.. This study was designed as qualitative study. It analyzed the form of word descriptively. This research used document analysis as its approach. During the process of research, the researcher collected the documents which were delivered In November 2016. The documents There are four Speeches of Obama's which are taken in AmericanRhetoric.com. The analysis was concern with types of grammatical cohesion (reference and conjunction). After analyzing the data the reseacher found the are grammatical cohesion on Obama's speeches. There are three functions of grammatical cohesion found within the speech. The researcher found the types of grammatical cohesion are reference and conjunction. There are 9.662 data found on four speeches. Where the reference has 6.746 items and conjunction 2.816 items. The grammatical cohension are: First, the mostly used of the reference was 70,55% while conjunction was 29,45%. Reference has three important functions ; (1) to avoid repeating the same words, (2) to point out a scale of proximity, and (3) to compare something or situation. Second is conjunction, it has five functions are (1) to relate similar or identical words, (2) to coordinate sentences which have the same context, (3) to support previous sentence, (4) to opposite the preceding statement, and (5) to connect between cause and effect in a sentence. Third, the general and basic function of grammatical cohesion is to relate words, clauses, phrases, or sentence in order to make the sentence meaningful.